Prospective observational study to evaluate the use of musculoskeletal ultrasonography in rheumatoid arthritis management: the ECHO study - Stein, Michael; Vaillancourt, Julie; Rampakakis, Emmanouil; Sampalis, John S (Rheumatology (Oxford, England), 2020)
Since the creation of the Canadian Rheumatology Ultrasonography Society, an increasing number of rheumatologists has been trained in the use of musculoskeletal US (MSUS). We compared the effectiveness of MSUS to routine care (RC) as a disease management tool in patients with moderate-to-severe RA requiring a treatment change due to lack of efficacy. The predictive value of MSUS was also assessed. This was a prospective, two-cohort, quasi-experimental study. Patients were managed either with MSUS (within the Canadian Rheumatology Ultrasonography Society) or as per RC for up to 1 year. Main outcomes included Clinical Disease Activity Index low disease activity/remission, DAS28 low disease activity/remission, MSUS scores, patient satisfaction and perception of participation in disease management. A total of 383 patients were enrolled (MSUS: n = 171; RC: n = 212). At baseline, a greater proportion of MSUS patients were treated with a biologic DMARD (50.3 vs 36.8%; P = 0.008) while more patients treated per RC received a non-biologic DMARD (84.2 vs 91.5%; P = 0.027). During follow-up, a greater number of RA treatment modifications was applied in the MSUS group compared with RC [adjusted incidence rate ratio (95% CI): 1.4 (1.1, 1.8)], including steroids, non-biologic DMARDs and biologic DMARDs. Regarding clinical and patient-reported outcomes, no remarkable differences were observed between groups. However, throughout the study, 50-80% of MSUS patients in clinical remission has a MSUS synovitis score of ≥1, and 37-73% an erosion score of ≥1. Significant associations were observed between baseline synovitis and joint erosion during follow-up. MSUS assessments can be useful in detecting subclinical levels of inflammation and predicting future joint deterioration, thus allowing optimization of RA treatment and patient care.